Acclimating Cucumber Plants to Blue Supplemental Light Promotes Growth in Full Sunlight - Kang, Chenqian; Zhang, Yuqi; Cheng, Ruifeng; Kaiser, Elias; Yang, Qichang; Li, Tao (Frontiers in Plant Science, 2021)
Raising young plants is important for modern greenhouse production. Upon transfer from the raising to the production environment, young plants should maximize light use efficiency whilst minimizing deleterious effects associated with exposure to high light intensity. The light spectrum may be used to establish desired traits, but how plants acclimated to a given spectrum respond to high light intensity exposure is less well explored. Cucumber (Cucumis sativus) seedlings were grown in a greenhouse in low-intensity sunlight (control; ~2.7 mol photons m-2 d-1), and were treated with white, red, blue or green supplemental light (4.3 mol photons m-2 d-1) for ten days. Photosynthetic capacity was highest in leaves treated with blue light, followed by white, red and green, and was positively correlated with leaf thickness, nitrogen and chlorophyll concentration. Acclimation to different spectra did not affect the rate of photosynthetic induction, but leaves grown under blue light showed faster induction and relaxation of non-photochemical quenching (NPQ) under alternating high and low light intensity. Blue light acclimated leaves showed reduced photoinhibition after high light intensity exposure, as indicated by a high maximum quantum yield of photosystem II photochemistry (Fv/Fm). Although plants grown under different supplemental light spectra for ten days had similar shoot biomass, blue-light grown plants showed a more compact morphology with smaller leaf area and shorter stems. However, after a subsequent, week-long exposure to full sunlight (10.7 mol photons m-2 d-1), blue light-grown plants showed similar leaf area and 15% higher shoot biomass, compared to plants had been acclimated to other spectra. The faster growth rate in blue light acclimated plants compared to other plants was mainly due to a higher photosynthetic capacity and highly regulated NPQ performance under intermittent high solar light. Acclimation to blue supplemental light can improve light use efficiency and diminish photoinhibition under high solar light exposure, which can benefit plant growth.